2000
DOI: 10.1038/sj.bdj.4800693
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of paired compomer and glass ionomer restorations in primary molars: final results after 42 months

Abstract: T echniques used to restore primary molar teeth have changed over the past decade as new adhesive materials have been developed. Stainless steel or nickel chrome preformed crowns provide the most durable restoration, often surviving until the tooth exfoliates. 1 The durability of other restorative materials are usually compared with dental amalgam. Composite resins in the short term are as durable as amalgam but after 6 years have a failure rate of 62% compared with 20% for amalgam after 5 years. 2 Conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 11 publications
4
13
0
Order By: Relevance
“…In the present study, the same RMGIC-P showed the highest failure rate and the shortest longevity of the restorations, while the results of another RMGIC, RMGIC-V, and the compomer were at the same or even higher level as that for class II amalgam restorations in the first part of the project (11). The superior findings for RMGIC-V and the compomer are supported by other studies (21)(22)(23)(24)(25)(26)(27)(28). Thus, it can be concluded that the increased tensile and flexural strength of the newly developed RMGIC and compomer materials have reduced the clinical shortcomings of earlier GIC and RMGIC materials.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, the same RMGIC-P showed the highest failure rate and the shortest longevity of the restorations, while the results of another RMGIC, RMGIC-V, and the compomer were at the same or even higher level as that for class II amalgam restorations in the first part of the project (11). The superior findings for RMGIC-V and the compomer are supported by other studies (21)(22)(23)(24)(25)(26)(27)(28). Thus, it can be concluded that the increased tensile and flexural strength of the newly developed RMGIC and compomer materials have reduced the clinical shortcomings of earlier GIC and RMGIC materials.…”
Section: Discussionsupporting
confidence: 83%
“…[123456] At the same time, there is evidence to support that conventional glass ionomer cement is inappropriate for use in primary molars due to its low physical properties and poor long-term performance. [789] These findings contradict the choice of materials made by clinicians worldwide.…”
Section: Introductionmentioning
confidence: 98%
“…It is suitable for class I and II restorations in primary teeth and is light cured [13]. Compomers have been shown to have comparable longevity to amalgam in primary teeth and are superior to conventional glass ionomer materials [14,15]. In addition to the benefits afforded by an adhesive material in terms of minimal cavity preparation and fluoride release on setting, the bright colour made it easier to place where visual access was limited.…”
Section: Discussionmentioning
confidence: 99%